2(nd) PEGS Annual Symposium on Antibodies for Cancer Therapy: April 30–May 1, 2012, Boston, USA - Ho, Mitchell (Landes Bioscience, 2012)
The 2nd Annual Antibodies for Cancer Therapy symposium, organized again by Cambridge Healthtech Institute as part of the Protein Engineering Summit, was held in Boston, USA from April 30(th) to May 1(st), 2012. Since the approval of the first cancer antibody therapeutic, rituximab, fifteen years ago, eleven have been approved for cancer therapy, although one, gemtuzumab ozogamicin, was withdrawn from the market.  The first day of the symposium started with a historical review of early work for lymphomas and leukemias and the evolution from murine to human antibodies. The symposium discussed the current status and future perspectives of therapeutic antibodies in the biology of immunoglobulin, emerging research on biosimilars and biobetters, and engineering bispecific antibodies and antibody-drug conjugates. The tumor penetration session was focused on the understanding of antibody therapy using ex vivo tumor spheroids and the development of novel agents targeting epithelial junctions in solid tumors. The second day of the symposium discussed the development of new generation recombinant immunotoxins with low immunogenicity, construction of chimeric antigen receptors, and the proof-of-concept of ‘photoimmunotherapy’. The preclinical and clinical session presented antibodies targeting Notch signaling and chemokine receptors.  Finally, the symposium discussed emerging technologies and platforms for therapeutic antibody discovery.